2004
DOI: 10.1080/02841860410026170
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of arm and shoulder mobility and strength after modified radical mastectomy and radiotherapy

Abstract: Seventy-five women, of whom 30 had received postoperative radiotherapy, were tested for range of motion (ROM) and shoulder strength with a goniometer and an isokinetic device (Orthotron II), respectively. On the individual level, irradiated patients exhibited significantly reduced range of motion (varying from p < 0.05 to p < 0.001) for all movements compared with the non-operated side. In contrast, in the non-irradiated patients only flexion was significantly reduced (p < 0.05). The same individual pattern wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
3
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 11 publications
4
48
3
1
Order By: Relevance
“…Blomqvist et al 17 evaluated 75 women who had undergone modified radical mastectomy (30 of them received RT) and found that radiation was the greatest cause of impaired ROM. These investigators concluded that patients undergoing RT should be PG: Physical therapy Group; CG: Control Group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Blomqvist et al 17 evaluated 75 women who had undergone modified radical mastectomy (30 of them received RT) and found that radiation was the greatest cause of impaired ROM. These investigators concluded that patients undergoing RT should be PG: Physical therapy Group; CG: Control Group.…”
Section: Discussionmentioning
confidence: 99%
“…The segment undergoing evaluation needed to be in the anatomical position, with the proximal segment stabilized so as to permit only the desired joint motion. The women were asked to perform active motion so as to reach the greatest range possible, and the angles were recorded in degrees 17,19 .…”
Section: Range Of Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, strength was found to be diminished on the operative side, worse when combined with radiation therapy [56,57]. In addition to upper extremity complications, postural effects commonly ensue, and postural failures are seen in 83% of breast cancer survivors as a result of treatment [58].…”
Section: Loss Of Functionmentioning
confidence: 99%
“…Surgical treatment and radiation can result in significant upper body limitations [3][4][5] including impaired range of motion [6,7], reduction in muscle activity [8], and the development of lymphedema [9] which can lead to a reduction in quality of life and psychological distress [10]. Chemotherapy is commonly used as an adjuvant treatment to reduce the likelihood of metastasis [2].…”
Section: Introductionmentioning
confidence: 99%